Dietary insulin index and load with risk of breast cancer in a case‐control study. Issue 12 (5th October 2021) - Akbari, Atieh; Sohouli, Mohammad Hassan; Deliu Lozovanu, Oana; Lotfi, Mojtaba; Nabavizadeh, Raheleh; Saeidi, Reza
Abstract: Objective: Circulating insulin levels have been positively associated with risk of breast cancer (BrCa); however, it remains unclear whether a diet inducing an elevated insulin response influences Breast risk. Methods: In this study, 250 newly diagnosed breast cancer patients and 250 hospitalised controls were recruited using convenience sampling. The dietary insulin index (DII) was calculated by dividing the dietary insulin load by the total energy intake. Results: Compared with those in the lowest tertiles of DII and dietary insulin load (DIL), subjects in the highest tertile were more likely to be overweight, have a family history of breast and other types of cancer and a history of benign breast diseases. After controlling for multiple potential confounders, a significantly increased BrCa odds was observed in the highest tertiles of DII and DIL score compared with the lowest tertiles (odds ratio (OR): 1.46; 95% CI: 0.67‐3.19, P  = .006) and (OR: 1.87; 95% CI: 0.92‐3.80, P  = .038), respectively. Conclusions: Our findings suggest that a diet that induces an elevated postprandial insulin response, indicated by higher DII and DIL scores, may increase the odds of BrCa, especially among women.